The impacts of working 12-hour shifts in the emergency Department on physicians' health, social life, and decision-making: a cross-sectional study - Yahia Akeely; Mutaz Mousa Alharbi; Swaid Raza Saulat; Albaraa Mehdar; Naif Misfer Alzhrany; Fahad M. Samarkandy; Gary M. Vilke; Saleh Alesa (Saudi Journal of Emergency Medicine)
Background: Currently, the demand for emergency medicine physicians is much higher than the available workforce. To overcome this issue, some institutions have increased their working hours. No previous study in Saudi Arabia addresses this issue and its impacts on physicians. Aim of the study: this study evaluates physicians health, social life, and decision making in 12 hours shifts compared against regular 8 hours. Methods: This cross-sectional study was conducted in various cities and hospitals in the Kingdom of Saudi Arabia using a questionnaire that surveyed 173 emergency physicians working in different hospitals across Saudi Arabia. Results: There were many similarities and differences between the participants who worked 12-hour shifts and those who worked 8-hour shifts. The most significant differences were that those who worked 12-hour shifts were more likely to be male than female and more likely to be married than unmarried. In addition, the 12-hour working physicians had more nonworking partners than the 8-hour group. Furthermore, they had less time for socialization with friends. Changes in blood sugar levels and headache were more common in the 12-hour group. Both groups had a similar incidence of COVID-19, physical illnesses, and the use of sedative medications. The two groups showed almost the same decision-making abilities. On the other hand, only 8.1% of those working 12-hour shifts wanted to continue working 12-hour shifts, and 69.1% in the 8-hour group wanted to continue working 8-hour shifts. Conclusion: Both 8- and 12-hour shifts appear feasible and safe. [SJEMed 2021; 2(3.000): 244-249]